Pengaruh Nilai Tukar, Investasi Asing Langsung, Impor dan Harga Minyak Dunia Terhadap Pertumbuhan Ekonomi Indonesia - Devi Kartika; Ambya (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Economic growth is the development of activities in a country's economy that produce goods and services produced by the community and increase people's welfare without ignoring equity and stability. Economic growth is related to the process of increasing the production of goods and services in the economic activities of society. To improve people's welfare, increased economic growth and an even distribution of income are needed. Factors affecting economic are the exchange rate, direct foreign investment, imports, and world oil prices. The analysis tool used is autoregressive distributed lag. Based on the results of research using time series data per quarter from 2000 to 2020, it shows that the exchange rate and imports have a significant negative effect on economic growth in Indonesia, both in the short and long term. FDI and WOP have a significant positive effect on economic growth in Indonesia, both in the short and long term.